Pengaruh Motivasi Kerja Dan Pengembangan Karir Terhadap Kinerja Pegawai Pada Kantor Bagian Umum Dan Kepegawaian Sekretariat DPRD Provinsi Banten - Abdul Fatah (CV ODIS, 2021)
This research aims to determine the influence of Work Motivation and Career Development on Employee Performance in the general office and staffing secretariat of the DPRD Banten Province. This research was conducted by survey method with a quantitative approach. The population of this study amounted to 200 employees and sampled 133 employees calculated using slovin’s formula. The research was conducted in the general and staffing office of the Secretariat of the DPRD of Banten Province from January 1 to 2019. The data was collected using questionnaires and analyzed with SPSS version 23. Based on the results of the study, it can be concluded that there is no influence of work motivation on employee performance, there can be an influence of career development on employee performance, and there can be a significant influence between Work Motivation and Career Development on Employee Performance.